2022
DOI: 10.1186/s12913-022-08471-8
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and work-privacy conflict – are there differences between full-time and part-time physicians?

Abstract: Background Changes in everyday work with regard to working time models have reached the medical profession. The number of physicians working part-time is steadily increasing. At the same time, however, the population's need for care is also rising. This can reinforce the impending shortage of doctors in the future. The aim was to investigate differences in work-privacy conflict and burnout among physicians working full-time or part-time. Method The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…In short, they suggest that shorter work regimes are not accompanied by a lower burnout risk. In line with the previous study among physicians [ 15 ], our study also confirmed that female and younger individuals were more prone to developing burnout. However, in contrast to the previous study among physicians [ 15 ], our participants with schedule flexibility did not experience a lower burnout risk compared to participants with no schedule flexibility.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In short, they suggest that shorter work regimes are not accompanied by a lower burnout risk. In line with the previous study among physicians [ 15 ], our study also confirmed that female and younger individuals were more prone to developing burnout. However, in contrast to the previous study among physicians [ 15 ], our participants with schedule flexibility did not experience a lower burnout risk compared to participants with no schedule flexibility.…”
Section: Discussionsupporting
confidence: 92%
“…First, the results of our descriptive analysis confirmed that part-time work is not accompanied by lower burnout risk and that part-time employees experience the same (degree of) burnout symptoms as their full-time counterparts. These findings are similar to those of previous studies among physicians [ 15 ] and teachers [ 16 ] that found no objective differences in burnout risk among part-time and full-time employees.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations